Blockade of ZMIZ1‐GATA4 Axis Regulation Restores Youthfulness to Aged Cartilage - Jiho Nam; Hyunmin Woo; Jihye Yang; Seok Jung Kim; Kwang Pyo Lee; Ji Hoon Yu; Tae Joo Park; Seong‐il Eyun; Siyoung Yang (Advanced Science)
Abstract Susceptibility to cartilage degeneration increases in an age‐dependent manner and older cartilage exhibits increased catabolic factor expression leading to osteoarthritis (OA). While inhibition of cellular senescence can prevent age‐related diseases, the understanding of the regulators governing cartilage senescence and the potential for senolytic intervention remains limited. Here, in vitro and in vivo results are reported, demonstrating for the first time that the transcriptional regulator, ZMIZ1, is upregulated in aged and OA cartilage, and that it acts through GATA4 to accelerate chondrocyte senescence and trigger cartilage deterioration. Furthermore, it is shown that K‐7174 interferes with the ZMIZ1‐GATA4 interaction and effectively hampers cartilage senescence and OA. It is proposed that inhibition of the ZMIZ1‐GATA4 axis could be a valuable strategy for eliminating senescent chondrocytes and impeding OA development and that the relevant inhibitor, K‐7174, could potentially be developed as a senolytic drug for managing cartilage senescence and age‐related degeneration.